Programming for corpus linguistics : how to do text analysis with Java - Mason, Oliver (Edinburgh : Edinburgh University Press, 2000)
Specialised linguistic research needs can no longer be met by available software. This book enables the researcher to write programs for text and corpus processing, using the popular and easy to learn Java language
Includes bibliographical references (p. 235-236) and index
Keywords: Java (Computer program language); Computational linguistics